Health outcomes for youth with type 1 diabetes at 18 months and 30 months post transition from pediatric to adult care. (May 2018) - Farrell, K.; Fernandez, R.; Salamonson, Y.; Griffiths, R.; Holmes-Walker, D.J.
Abstract: Aims: To identify (a) determinants of glycated haemoglobin (HbA1c) at 18 and 30 months following transition in young people with Type 1 diabetes mellitus (T1DM) to a youth-specific diabetes service; and to (b) evaluate the impact of the service on acute admissions with diabetic ketoacidosis (DKA) over a 14-year period. Methods: An audit of records of youth with T1DM referred from paediatric services to the multidisciplinary transition service at Westmead Hospital, from 2001 to 2012, and followed-up to 2014. Results: Data from 439 adolescents and young adults (Median age: 18) were analysed. The recommended standard of glycaemic control, HbA1c < 7.5% (58 mmol/mol), was achieved by 23% at baseline, 22% at 18-months, and 20% at 30-month. After adjusting for lag time (>3 months) and diabetes duration (>7 years), glycaemic control at first visit predicted subsequent glycaemic control at 18-month and 30-month follow-up. From 2001 to 2014, only 8.6% were lost to follow-up; admissions and readmissions for DKA reduced from 72% (32/47) to 4% (14/340) ( p  < 0.001). Furthermore, mean length of stay (LOS) significantly decreased from 6.56 to 2.36 days ( p  < 0.001). Conclusions: Continuing engagement with the multidisciplinary transition service prevented deterioration in HbA1c following transition. Age-appropriate education and regular follow-up prevents DKA admissions and significantly reduced admission LOS.